Social Reality in The Novel CADL By Triskaidekaman: Antonio Gramsci Hegemonic’s Study - Ridha Illahi; Nensilianti Nensilianti; Faisal Faisal (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
Abstract This study aims to describe the form of coercion (threats) and forms of consensus (agreement) contained in the analyzed novel. This research is descriptive qualitative. The results of this study indicate that first, Coercive is a position where ruling party member threat to the party who mastered to achieve goals which is desired. Coercive form (threat) to the character Zaliman (Bagus) who applies a lot policies that are deemed unreasonable. The policy contains prohibitions and rules involving people's private lives and supported by strict supervision in its application, prohibitions such as the use of the vowel E in both pronunciation and writing. Second, convention is a agreement or agreement achieved through and mutual understanding for achieve what you want. The form of the convention (agreement) can be seen in the form of decision making by Zaliman (Bagus) and his cronies who dominate the minds of the people to agree to all the rules that have been set, such as the establishment of the basic constitution of Wiranacita.Keywords: Hegemony, Coercive, Consensus